Zakres odpowiedzialności odszkodowawczej ubezpieczeniowych funduszy gwarancyjnych - regulacje polskie a praktyka światowa - Janusz, Alicja (Liability Scope of Insurance Guarantee Funds Indemnity - Polish Regulations vs. World Practice, 2006)
Insurance guarantee funds are the institutions whose basic task is to compensate claims resulting from insurance policy of the entitled individuals in case of insurance company bankruptcy. In Poland this type of institution is represented by the Insurance Guarantee Fund (IGF). The objective of the hereby paper is to present the scope of IFG indemnity liabilities at the background of practices carried out in this field in other countries. The comparison was conducted considering: subjective and objective scope of guarantee functioning, as well as the mode of the guaranteed amount assessment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 260-271